Enhancement of LED based photocatalytic degradation of sulfolane by integration with oxidants and nanomaterials. (January 2021) - Dharwadkar, Sripriya; Yu, Linlong; Achari, Gopal
Abstract: In this study, oxidants and nanomaterials were used to improve titanium dioxide based photocatalytic degradation of sulfolane. Hydrogen peroxide (H2 O2 ), sodium persulfate (SPS) and ozone (O3 ) were the oxidants studied and carbon nanotubes (CNT) and nanosized zero valent iron (nZVI) were used as the nanomaterials. The impact of these oxidants and nanomaterials was evaluated at various dosages in both Milli-Q water and groundwater. The results indicate that with a suitable dose of oxidants or nanomaterials, photocatalytic degradation of sulfolane in Milli-Q water can be enhanced. The addition of ozone contributed to a significant increase in sulfolane degradation rate in Milli-Q water. The experiments conducted in groundwater showed that oxidants (H2 O2, SPS and O3 ) increased the degradation of sulfolane while the nanomaterials (CNT and nZVI) impeded sulfolane degradation in groundwater. Highlights: Enhancing photocatalytic degradation of sulfolane using H2 O2, persulfate and ozone. Integrating carbon nanotube with photocatalysis increased degradation by two times. Impact of nano-zerovalent iron on TiO2 photocatalysis shows two phase response. Photocatalytic degradation in groundwater improved up to 18 times using ozone.